Customizing analytical and advisory services for middle-income countries in the Latin America and Caribbean region (World Bank WashingtonUS, 2008)
Examines the changing nature of the Bank's analytic and advisory services in the LAC region. Describes four kinds of Analytic and Advisory Activities (AAA) provided namely, fee-based services; flexible programmatic assistance; support for electoral transitions; and, facilitating engagement among multiple stakeholders. Provides several principles on the provision of unbundled analytic and advisory services.
Keywords: KNOWLEDGE